Analisis Masa Kejayaan Islam di Bidang IPTEKS dan Hakikat IPTEKS dalam Islam Khususnya Bidang Manajemen - Purwanti Purwanti (ALSYS, 2025)
The study of Islam’s golden age in science, technology, and the arts (IPTEKS) is essential to understanding the foundations of Islamic civilization, which has made substantial contributions to the development of the modern world. This research focuses on the contributions of IPTEKS during the eras of Umar bin Khattab, the Umayyad and Abbasid dynasties, and the Ottoman Empire, while analyzing the application of IPTEKS principles within the context of management. The objective is to examine the relevance of classical Islamic achievements in IPTEKS to contemporary management principles, particularly in the fields of public administration, economics, education, and bureaucracy. A qualitative descriptive approach was employed, based on literature review and comparative analysis between historical managerial practices and modern management theories. The findings reveal that Umar bin Khattab pioneered transparent systems of public and fiscal management; the Umayyad dynasty strengthened governmental communication and monetary systems; the Abbasid dynasty institutionalized scientific governance through Bayt al-Hikmah and fostered innovation; and the Ottoman Empire implemented centralized bureaucracy while systematically managing waqf and public infrastructure projects. The study concludes that the essence of IPTEKS in Islamic civilization lies not merely in the accumulation of knowledge, but in the ethical, socially just, and sustainable application of management principles. These findings underscore the historical relevance of Islamic IPTEKS in informing modern, humanistic, and values-based management development.